The Effects of Social Capital on the Cultural Capital (Case Study: Teachers of Hamadan Province & Its City) - mehrdad hossein panahi; iraj saeiarasi; sasan vadiea (توسعه اجتماعی, 2016)
Cultural capital is one of the capital in the analysis of Bourdieu (1977), has been proposed. Following the introduction of the concept of cultural capital in the field of Jamh Shnasy, the researcher-is a variety of different titles to examine the relationship between cultural capital and other variables such as educational attainment focused. This study examines the impact of social capital, cultural capital of the subsidiary in the sample of 376 teachers in the province Vshhrstan's and Bourdieu's theory of cultural capital and Putnam to formulate hypotheses have been used. Cluster sampling methods for data collection and direction data, and the whole package is sent Lykrd use and population samples in each cluster were selected through random sampling, through spss software and amos Version 23 and using Frmlhay regression analysis of the way the data is argued that in the end the results obtained, in exchange for an increase in social capital, awareness, public confidence and participation of 50%, 43%, 29% and 31% increase in cultural capital is evident, and thus can be of significant impact on the dependent variable and independent variables (cultural capital) ratayyd.